"Those are things for married people" exploring parents'/adults' and adolescents' perspectives on contraceptives in Narok and Homa Bay Counties, Kenya - Jefferson Mwaisaka; Yohannes Dibaba Wado; Ramatou Ouedraogo; Clement Oduor; Helen Habib; Joan Njagi; Martin W. Bangha (BMC, 2021)
Abstract Background Contraceptive use among adolescent girls is low in many sub-Saharan African countries including Kenya. Attitude and perspectives about contraception of community members including adolescent girls themselves may be likely to limit contraceptive use among adolescent girls. This study was conducted to explore and compare adults'/parents' and adolescent girls' narratives and perspectives about contraception in Narok and Homa Bay counties, Kenya. Methods Qualitative data from 45 in-depth-interviews conducted with purposively selected consenting adolescent girls aged 15-19 was used. Additionally, twelve focus group discussions were held with 86 consenting adults conveniently recruited from the two counties. All discussions were conducted in the local language and audio recorded following consent of the study participants. Female moderators were engaged throughout the study making it appropriate for the study to solicit feedback from the targeted respondents. Results Findings highlighted adults' perceptions on adolescents' sexuality and the presence of stringent conceptions about the side-effects of contraception in the study communities. Some participants underscored the need for open contraceptive talk between parents and their adolescent girls. Four main themes emerged from the discussions; (i) Perceptions about adolescents' sexuality and risk prevention, (ii) Conceptions about contraception among nulligravida adolescents: fear of infertility, malformation and sexual libertinism, (iii) Post-pregnancy contraceptive considerations and (iv) Thinking differently: divergent views regarding contraceptives and parent/adolescent discussion. Conclusions Our findings suggest the need for increased attention towards adolescents and their caregivers particularly in demystifying contraceptive misconceptions. Programmatic responses and models which include the provision of comprehensive sexuality education and increased access to and utilization of SRH information, products and services through a well-informed approach need to be well executed. Programmatic efforts like SRH community education should further seek to enhance the capacity of parents to discuss sexuality with their adolescents.